Sufis and Sufism: some reflections - Misra, Neeru (Manohar Publishers & Distributors, 2004)
Contributed articles. - Ali, the first fata and the fourth caliph in the light of Indo-Persian and Central Asian historical sources / Mansura Haidar -- Mystical relations between Iran and India / Abdolrahim Gavahi -- Position and role of Khadim-i-Khas in Pir-Murid relations with special reference to Maulana Badruddin Isaq Dehalvi / S. Liaqat H. Moini -- Divine love in sufism ans bhakti-marga (Kabir Das and Sri Ramakrishna) / Ninel Ghaffurova -- Sufis and their contribution in the process of urbanization / maksud Ahmad Khan -- Impact of Ibn "Arabi"s mystical thought on the sufis of India during the sixteenth century / Iqbal Sabir -- A rare Suhrawardy manuscript of late fourteenth century AD: the Malfuzat of Shaikh Akhi Jamshed Rajgiri / Maksud Ahmad Khan -- Mir Saiyid Ali Hamadani: as depicted in the sources / Mansura Haidar.